1980
DOI: 10.1128/jcm.11.4.430-432.1980
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of autoagglutination and virulence of yersiniae

Abstract: Virulent strains of Yersinia pestis, Y. pseudotuberculosis and Yersinia enterocolitica invariably autoagglutinated in tissue culture media when grown at 36°C. Avirulent strains did not possess this property. Yersinia pestis, Y. pseudotuberculosis, and Y. enterocolitica are animal pathogens which can cause a diversity of human disease. Y. pestis, the causative agent of bubonic plague in humans, is highly infectious and lethal to most rodents and many small mammals. Y. pseudotuberculosis and Y. enterocolitica, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(144 citation statements)
references
References 1 publication
5
139
0
Order By: Relevance
“…The identification of yersiniae was performed by the methods of Wauters et al (1988). All isolates identified as yersiniae were subjected to autoagglutination tests to evaluate their potential pathogenicity (Laird and Cavanaugh, 1980). Then, virulent isolates were subjected to further analysis.…”
Section: Isolation and Identification Of Yersiniamentioning
confidence: 99%
“…The identification of yersiniae was performed by the methods of Wauters et al (1988). All isolates identified as yersiniae were subjected to autoagglutination tests to evaluate their potential pathogenicity (Laird and Cavanaugh, 1980). Then, virulent isolates were subjected to further analysis.…”
Section: Isolation and Identification Of Yersiniamentioning
confidence: 99%
“…A number of studies (McDermott et al 1993;Goverde et al 1994) have shown that the choice of incubation temperature affects the growth kinetics of plasmid-bearing and plasmid-cured strains of Escherichia coli and Y. enterocolitica. In general, virulence plasmid expression in Yersinia occurs at temperatures > 30 C, this expression is usually observed in phenotypic characteristics such as calcium dependency, autoagglutination and production of outer membrane proteins (Laird and Cavanaugh 1980;Cornelis et al 1987;Bhaduri et al 1990). Goverde et al (1994) reported that virulence plasmid expression at temperatures greater than 30 C retards the growth rate of plasmid-bearing Y. enterocolitica strains as plasmid replication places an additional metabolic burden on growing cells.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature outside the host fluctuates and is usually tess than 2,7''C, while the environment Inside the host is thermally regulated at 37°C; consequently, several Y. enteroootitioa virulence genes are regulated by temperature and other host stimuli to facilitate the hostpathogen interaction. Pathogenic Yersinia species harbour a related 70 kb virulence piasmid that encodes many thermally regulated virulence phenotypes such as autoagglutinability (Laird and Cavanaugh, 1980), cytotoxicity (Portnoy et ai, 1981), and serum resistance (Pai and DeStephano, 1982). The invasive phenotype of Y. enterocoiitica is only associated with pathogenic strains and is regulated by growth temperature (Lee et al, 1977;Miller etai, 1989;Pierson and Falkow, 1990;Schiemann and Devenish, 1982).…”
Section: Introductionmentioning
confidence: 99%